2023
DOI: 10.1111/sum.12931
|View full text |Cite
|
Sign up to set email alerts
|

Sewage sludge treated with bentonite, vermiculite or biochar can improve soil properties and enhance growth of grasses

Abstract: Sewage sludge treated with 15% bentonite, vermiculite or biochar was evaluated as a soil amendment in comparison to limed and untreated sludge. Seven treatments were established to two soils, an acid and an alkaline, in three replications, i.e. 2% addition of sludge treated with bentonite, vermiculite, biochar and lime and application of 2% untreated sludge, inorganic fertilization and no sludge or inorganic fertilizers (control). Then, the soil treatments were used in a pot experiment with perennial ryegrass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Vermiculite is chemically inert, biologically stable, and non-combustible. It has a high sorption capacity and buffering properties [55][56][57][58].…”
Section: Vermiculite Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Vermiculite is chemically inert, biologically stable, and non-combustible. It has a high sorption capacity and buffering properties [55][56][57][58].…”
Section: Vermiculite Characteristicsmentioning
confidence: 99%
“…Vermiculite is also employed as a filtering material in the food industry, a carrier in animal feeds, or a sorbent in environmental protection. Vermiculite's ability to absorb and store a significant amount of water and cations, gradually releasing them, characterizes it as an excellent buffering material influencing the maintenance of optimal soil pH, aeration, and nutrient retention [55][56][57][58]. The vermiculite used in the experiment was purchased from Sobex company (Drezdenko, Poland).…”
Section: Vermiculite Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies [e.g., (Ruan et al 2023;Li et al 2019;Zhang et al 2019)] have demonstrated that adding functional biochar to AD of WAS can effectively immobilize heavy metals and reduce environmental risks. Athanasios et al (Balidakis et al 2023) further assessed the effectiveness of sludge amended with biochar as a soil amendment. Research has shown that adding biochar significantly improved soil organic matter and fertility.…”
Section: Soil Amendmentmentioning
confidence: 99%